Dispensasi Nikah: Analisis Kontemporer Dimensi Pernikahan Dini Menurut Berbagai Aktor di Kabupaten Bantul D.I Yogyakarta - Hilyasani, Faida; Najib, Agus Moh; Harahap, Reiki Nauli (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The phenomenon of early marriage or marriage dispensation continues to experience a surge, although it has dropped in 2020. Early marriage is considered as a social problem because it violates laws, regulations, and norms in some Indonesian societies. The study was conducted at the Bantul District Religious Court. The purpose of this study is to find out the meaning of the granting of marriage dispensation by the state and the opinions of various actors to the phenomenon of early marriage. This research was conducted using qualitative methods and interperative descriptive techniques. This research reveals the meaning of early marriage as a reality in society. The results of the study stated that there are various factors that cause early marriage or the granting of marriage dispensation, namely pregnancy before marriage, economic factors, educational factors and environmental factors. The granting of marriage dispensation by religious courts is carried out on the basis of four things, namely instrumental acts of rationality, rational actions of indigo, affective actions and traditional actions.